Acceptability of Multiparticulate Dosing Using Sympfiny® Delivery System with Children (Age 1-12) - Kate Abeln; Kate Cox; Laura Haggerty; Mary Beth Privitera (MDPI AG, 2022)
This study investigated multiparticulate formulation administered over a two-week period of time via the Sympfiny® system with children of ages 1-12 years. The study was conducted with parent-child pairs (N = 120 total participants) following a specific dose strategy to mimic PURIXAN's dosing guidelines based upon the child's age. PURIXAN® (mercaptopurine) and Methotrexate have been identified as potential chemotherapy drugs that could benefit from reformulation into multiparticulate. Multiparticulate drugs have advantages as they can be flavorless, and do not require liquid reconstitution and do not require refrigeration. The study included three parts: initial in-person session, 14 days of at-home use, and a final in-person session. The in-person sessions were conducted at HS Design's (HSD) (Morristown, NJ, USA) offices located in Morristown, New Jersey, where a study moderator captured and recorded all subjective comments by participants and observed device use to identify use errors. The participants were instructed to administer a dose (placebo) for the next 14 days and at each dose delivery to fill out a daily survey regarding their experience. Overall, the cumulative survey responses and feedback collected during the in-person sessions suggest that child participants ages 5-12 years old found multiparticulate to be an acceptable formulation and would be willing to take this medication if they were sick. Over time, more children ages 1-4 did not open their mouths; consistently around 15-20% of 1-4 years olds spat the placebo. However, approximately 95% of parents found the Sympfiny® system acceptable and indicated that they would use it to deliver medication to their child.